Evaluation of cytotoxic activity OFL-Asparaginase from marine BKJM2 against Jurkat J6 and PA1 celllines - M.BHARGAVI; R. JAYA MADHURI (International Journal of Pharma and Bio Sciences, 2017)
Cancer is most prevalent disease occurring in human beings now a days. Cancer remains the second leading cause of death in the world. In its projection, the Indian Council of Medical Research (ICMR) said in 2016 the total number of new cancer cases is expected to be around 14.5 lakh and the figure is likely to reach nearly 17.3 lakh new cases in 2020. L-Asparaginase is an anti-neoplastic agent used in the chemotherapy of acute lymphoblastic leukemia. L-Asparaginase producing marine microorganisms are isolated from coastal area of Kerala. Among 10 isolates were isolate, out of 10 isolates only one showed a potent positive result for L-Asparaginase production on screening and named as BKJM2. Marine isolate (BKJM2) was tested for invitro cytotoxic activity using MTS assay against Jurkat J6(Leukemia cell line) and 3-(4, 5-dimethyl-2-thiazolyl)-2, 5- diphenyl tetrazolium bromide (MTT) on Pa1 (Ovarian cancer cell line).The IC50 (Inhibitory concentration 50) was calculated as 8.27% of the purified enzyme. L-Asparaginase inhibited the growth of both cell lines. L-Asparaginase from BKJM2 did not show any effect on normal human cells indicating that the purified enzyme have high potential for selective cytotoxicity on cancer cells.